NOVEL PAJANG KARYA WAWAN SUSETYA SEBAGAI MATERI PEMBELAJARAN SASTRA: SOSIOLOGI SASTRA DAN NILAI PENDIDIKAN KARAKTER - Ridho Aji Perdana; Herman J Waluyo; Budi Waluyo (Universitas Sebelas Maret, 2019)
This research aims to explain: (1) social background of Pajang novel writer; (2) the sociological background of Pajang novel by Wawan Susetya; (3) readers' responses to Pajang's novel by Wawan Susetya; (4) the value of character education contained in Pajang's novel by Wawan Susetya; and (5) the relevance of Pajang's novel by Wawan Susetya as a literary learning material in high school. This research uses descriptive qualitative method and using a study of sociology of literature. The result of this research is description about: (1) social background of Pajang novel writer covering aspect of race, moment (moment), and environment (milieu); (2) Sociological background of Pajang's work by Wawan Susetya includes social group, culture, social institution, stratification, and power; (3) readers' responses to Pajang's novel by Wawan Susetya; (4) the value of character education contained in the Pajang novel by Wawan Susetya include religious, tolerance, hard work, democratic, curiosity, nationalism, achievement, friendly / communicative, social, and responsibility; (5) the relevance of Pajang's novel by Wawan Susetya as a literary learning material in Senior High School which is adapted to the content aspect, presentation aspect, language aspect, and graphictions aspect.